The best of Iggy (Lit. Circle) - Barrows, Annie (New York : G. P. Putnam's Sons, 2020)
Relates three times that nine-year-old Iggy got into trouble, two of which he does not regret and one for which he is very, very sorry.
3-6.
3.7.
550L
OBOB Elementary 2022-23.
Keywords: Behavior -- Fiction; Friendship. -- Juvenile fiction; Human behavior -- Juvenile fiction; Humor; Book sets; Literature circles